2021
DOI: 10.3390/molecules26113202
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Tetrasubstituted α-Aminophosphonic Acid Derivatives

Abstract: Due to their structural similarity with natural α-amino acids, α-aminophosphonic acid derivatives are known biologically active molecules. In view of the relevance of tetrasubstituted carbons in nature and medicine and the strong dependence of the biological activity of chiral molecules into their absolute configuration, the synthesis of α-aminophosphonates bearing tetrasubstituted carbons in an asymmetric fashion has grown in interest in the past few decades. In the following lines, the existing literatures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 113 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…However, the application of alafosfalin in medicine is limited due to its instability. It is shown that the correct design of the alkoxyl groups in the H -phosphite used for these compounds may significantly increase their antimicrobial properties ( Figure 1 ) [ 1 , 2 , 3 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of alafosfalin in medicine is limited due to its instability. It is shown that the correct design of the alkoxyl groups in the H -phosphite used for these compounds may significantly increase their antimicrobial properties ( Figure 1 ) [ 1 , 2 , 3 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction also can be promoted by heating or microwave irradiation ( Kaboudin and Nazari, 2001 ; Ranu and Hajra, 2002 ; Macarie et al, 2019 ). In recent years, asymmetric synthesis of aminophosphonates has also been reported ( Maestro et al, 2018 , 2019 ; Maestro et al, 2020 ; Maestro et al, 2021 ).…”
Section: Synthetic Methods For the Preparation Of Hydroxy- And Amino-...mentioning
confidence: 99%
“…The first can serve as surrogates for amino acids and reveal a broad spectrum of biological activity. [1][2][3][4][5][6][7][8][9][10] Phosphonamides, on the other hand, can be considered as analogues of the transition state of the hydrolysis of the peptide bond and are potent inhibitors of peptidases. 11 In addition, C,N-transfer of the phosphonyl group allows interconversions of aminophosphonates and phosphonamides.…”
Section: Introductionmentioning
confidence: 99%